Transcription of ribosomal component genes and lac in a relA+/relA pair of Escherichia coli strains. - Little, R (1984)
To determine the stringent response, a repression of gene activity during amino acid starvation assumed to be mediated by the effector necleotide guanosine tetraphosphate (ppGpp), of metabolically regulated constitutive genes, we measured the transcription of ribosomal protein genes, the constitutive lac operon, and stable RNA genes in a variety of growth media and after amino acid starvation in a relA+/relA pair of Escherichia coli B/r strains. For rRNA and tRNA (stable RNA) it has previously been shown that the distinction between stringent control and growth rate control is unfounded, as the function describing the stable RNA gene activities at different concentrations of guanosine tetraphosphate is independent of growth conditions (exponential growth or amino acid starvation) and of the relA allele present. Here, the results indicated that the stringent responses of ribosomal protein genes and lac differ from their metabolic control during exponential growth in different media. This can be explained by polarity and RNA polymerase sink effects during amino acid starvation which are irrelevant for stable RNA genes but which are superimposed on mRNA gene activities.